2006
DOI: 10.4038/jas.v2i1.8117
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge as a key to sustainable development

Abstract: Indigenous knowledge is the unique knowledge confined to a particular culture or society. It is also known as local knowledge, folk knowledge, people's knowledge, traditional wisdom or traditional science. This knowledge is generated and transmitted by communities, over time, in an effort to cope with their own agroecological and socioeconomic environments (Fernandez, 1994). It is generated through a systematic process of observing local conditions, experimenting with solutions and readapting previously identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(76 citation statements)
references
References 4 publications
(3 reference statements)
1
72
0
3
Order By: Relevance
“…This shows that the young farmers have a considerable level of awareness about water pollution. Education level does not reflect any significant contribution to the awareness on water pollution, However, this could be due to farming knowledge been passed through generations to generation by word of mouth (Senanayake, 2006) which influenced farmers to be mindful on water pollution even though they have not had formal education. Amarasekara et al (2013) reported that awareness on nutrient pollution was limited among farmers.…”
Section: (C) Awareness Of the Farmers About Water Quality And Water Pmentioning
confidence: 99%
“…This shows that the young farmers have a considerable level of awareness about water pollution. Education level does not reflect any significant contribution to the awareness on water pollution, However, this could be due to farming knowledge been passed through generations to generation by word of mouth (Senanayake, 2006) which influenced farmers to be mindful on water pollution even though they have not had formal education. Amarasekara et al (2013) reported that awareness on nutrient pollution was limited among farmers.…”
Section: (C) Awareness Of the Farmers About Water Quality And Water Pmentioning
confidence: 99%
“…Duration of stay in locality: Indigenous method base is local because it is produced from its surroundings, the economic and social activities and a unique environment. In other words, indigenous knowledge can better be grasped through a prolonged stay in an environment (Kloppenburg Jr, 1991;Senanayake, 2006;Zambrana et al, 2014).…”
Section: Age Of the Farmermentioning
confidence: 99%
“…Farming experience: Indigenous method is a function of practical engagement in everyday life which is reinforced through experience (Senanayake, 2006). Thus, long exposure to farming brings about familiarization, perfection and specialization with the use of indigenous methods (Usman et al, 2015).…”
Section: Age Of the Farmermentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous technology is referred to as local or traditional knowledge, folk knowledge, people's knowledge, traditional wisdom or traditional science (Senanayake, 2006). It is expressed through indigenous knowledge, methods and processes of agriculture, food preparation and conservation, health care and education (Senanayake, 2006). There are tangible and intangible forms of technology, with culture lying at the heart of all of them (Custer, 1995;Ogunbure, 2011).…”
Section: The Statement Should Rather Have Been Formulated As: Learnermentioning
confidence: 99%